Economics and Ethics: Heritage of Amartya Sen - Levent, Adem (Igiad-Turkish Entrepreneurship & Business Ethics Assoc, 2013)
Amartya Sen is currently working on enriching the discipline of economics through the introduction of new propositions. One of these propositions, developed by himself and based on Adam Smith, is an approach to economy in harmony with ethics. According to Sen, economy has two separate origins; engineering and ethics. For him, no example of two forms, such as ethics and engineering, can be considered to be completely pure in any sense. The real problem in economics is the problem of balance between these two approaches. According to Sen, many spokespeople advocating an ethical approach, from Aristotle to Adam Smith, have also shown a deep interest in various aspects of engineering within the general frame described by ethical reasoning. For this reason, these two origins should be balanced which means to review the concepts of the discipline; among them being rationality, utilitarianism, and Pareto Optimality. The review or criticism of these concepts is not intended to unsettle the orthodox/prevailing approach of economy, but is rather an effort to sort out the conflicting points within the discipline and to search for ways to increase functionability. Along with Sen's work, the study has been strengthened through the inclusion of other works that refer to the relationship between ethics and economy in an attempt to see the objective of Sen's ethics based argumentations. Thus, the objective of Sen's ethics based proposition is to develop the discipline within the contexts laid out by the orthodoxy and then to expand this discipline to as many other social sciences as possible. With this in mind however, Sen's proposal is still quite far from being a proposition or argument developed as part of the heterodoxy.
Keywords: Amartya Sen; Ethics; Orthodox Economy; Rational Behavior; Utilitarianism